Metadata-Driven Construction of Semantic Views in Enterprise Knowledge Graphs with LLM Agents - Vidal Rolim, Tulio; Freitas, José Renato S.; Vidal, Vânia Maria Ponte (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD), 2025)
An Enterprise Knowledge Graph (EKG) provides a robust foundation for knowledge management, data integration, and advanced analytics within organizations by offering a semantic view that unifies and semantically integrates heterogeneous data sources from the data lake. The data integration process remains complex and time-consuming due to schema mismatches, divergent terminologies, and inconsistencies in data collection practices. Recent advances in large language models (LLMs) have shown promise in addressing these challenges by assisting with various data integration tasks. This paper introduces a modular, agent-oriented architecture that supports the incremental and interactive construction of semantic views for EKGs. The architecture leverages LLM-powered agents in conjunction with a metadata graph that captures rich contextual information about each semantic view. This metadata graph plays a central role in enabling automation, enhancing explainability, and ensuring reusability throughout the construction process. By forming agent decisions in structured and trustworthy metadata, the proposed framework facilitates the development of semantic views of enterprise knowledge graphs.